To Cut or not to Cut: Can Large Periapical Cysts be Treated by Endodontic Treatment only? - MHK Motamedi (Wolters Kluwer Medknow Publications, 2010)
Introduction: The periapical cyst originates from the epithe-lium in a granuloma and is frequently associated with an inflammatory response to a necrotic pulp. This condition is clinically asymptomatic but can result in a slow-growth, bone resorption and swelling in the affected region.The hypothesis: Some authors support that if the endodontic infection is eliminated, the immune system is able to promote lesion repair, while others believe that surgical intervention is invariably nec-essary to remove cyst epithelium. This hypothesis indicates that large periapical cysts may be treated by only nonsurgical endodontic treatment.Evaluation of the hypothesis: Radicular cysts exist in two structurally distinct classes namely, those containing cavities completely enclosed in epithelial lining (periapical true cysts) and those containing epithelium-lined cavities that are open to the root canals (periapical pocket cysts). From a clinical point of view a periapical pocket cyst may heal after conventional root canal therapy whereas an apical true cyst is less likely to be resolved without surgical intervention. During the endodontic therapy of teeth associated with periapi-cal cysts, root canal instrumentation could be done slightly beyond the apical foramen. This will produce a transitory acute inflammation and destruction of the protective epithelial layer of the cyst, converting it into a granulated tissue, which has better resolution. Instru-mentation beyond the apical foramen could be carried out because it would help in cyst resolution through the relief of the intra-cystic pressure.